A multivariate view of the speciation continuum. (8th December 2022) - Bolnick, Daniel I; Hund, Amanda K; Nosil, Patrik; Peng, Foen; Ravinet, Mark; Stankowski, Sean; Subramanian, Swapna; Wolf, Jochen B W; Yukilevich, Roman
Abstract: The concept of a "speciation continuum" has gained popularity in recent decades. It emphasizes speciation as a continuous process that may be studied by comparing contemporary population pairs that show differing levels of divergence. In their recent perspective article in Evolution, Stankowski and Ravinet provided a valuable service by formally defining the speciation continuum as a continuum of reproductive isolation, based on opinions gathered from a survey of speciation researchers. While we agree that the speciation continuum has been a useful concept to advance the understanding of the speciation process, some intrinsic limitations exist. Here, we advocate for a multivariate extension, the speciation hypercube, first proposed by Dieckmann et al. in 2004, but rarely used since. We extend the idea of the speciation cube and suggest it has strong conceptual and practical advantages over a one-dimensional model. We illustrate how the speciation hypercube can be used to visualize and compare different speciation trajectories, providing new insights into the processes and mechanisms of speciation. A key strength of the speciation hypercube is that it provides a unifying framework for speciation research, as it allows questions from apparently disparate subfields to be addressed in a single conceptual model.